2008
DOI: 10.1007/s12031-008-9069-3
|View full text |Cite
|
Sign up to set email alerts
|

SEPS1 Gene is Activated during Astrocyte Ischemia and Shows Prominent Antiapoptotic Effects

Abstract: Contrarily to neurons, astrocytes can survive short periods of ischemia. We have searched for genes implicated in astrocyte resistance to ischemia using oxygen and glucose deprivation (OGD) as a stroke model. A RNA differential display approach uncovered the OGD induction of selenoprotein-S-encoding gene SEPS1. This endoplasmic reticulum (ER) resident protein is known to promote cell survival regulating the ER stress as well as inflammation. We found that suppression of SEPS1 by small interfering RNA severely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
5
29
0
Order By: Relevance
“…In these experiments performed with mouse astrocyte cultures, SelS expression was either (1) abrogated by siRNA technology or (2) increased through infection with an adenoviral vector harboring the complete human SelS coding sequence (AdSelS). According to our own observations, SelS siRNA reduces SelS mRNA expression in astrocytes to less than 1% (Fradejas et al, 2008), while transduction with AdSelS sharply increases it (Fig. 6A,B).…”
Section: Sels Controls Er-stress and Inflammatory-responses In Cultursupporting
confidence: 56%
See 3 more Smart Citations
“…In these experiments performed with mouse astrocyte cultures, SelS expression was either (1) abrogated by siRNA technology or (2) increased through infection with an adenoviral vector harboring the complete human SelS coding sequence (AdSelS). According to our own observations, SelS siRNA reduces SelS mRNA expression in astrocytes to less than 1% (Fradejas et al, 2008), while transduction with AdSelS sharply increases it (Fig. 6A,B).…”
Section: Sels Controls Er-stress and Inflammatory-responses In Cultursupporting
confidence: 56%
“…Even though direct evidence of SelS expression in brain astrocytes has not been obtained yet, a search for ischemia-induced genes led us to identify SelS in mouse primary astrocyte cultures (Fradejas et al, 2008). Moreover, in this study, we provided evidence that SelS supports survival of cultured astrocytes subjected to ischemia.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Furthermore, the astrocyte-targeted overexpression of superoxide dismutase 2 or heat shock protein 72 significantly reduces the loss of CA1 hippocampal neurons in a forebrain ischemia model [29]. In a recent study, Soledad Calvo et al found that inhibition of selenoprotein S1 by small interfering RNA severely increases astrocyte injury caused by OGD, suggesting that selenoprotein S protects astrocytes against ischemia [30]. Connexin43, a principal gap junction protein of astrocytes, is involved in protection from ischemic injury.…”
Section: Discussionmentioning
confidence: 99%